Homozygous variant in OTX2 and possible genetic modifiers identified in a patient with combined pituitary hormone deficiency, ocular involvement, myopathy, ataxia, and mitochondrial impairment. Issue 5 (17th February 2019) - Catania, Alessia; Legati, Andrea; Peverelli, Lorenzo; Nanetti, Lorenzo; Marchet, Silvia; Zanetti, Nadia; Lamperti, Costanza; Ghezzi, Daniele
Abstract : Here we report on a singleton patient affected by a complicated congenital syndrome characterized by growth delay, retinal dystrophy, sensorineural deafness, myopathy, ataxia, combined pituitary hormone deficiency, associated with mitochondrial impairment. Targeted clinical exome sequencing led to the identification of a homozygous missense variant in OTX2 . Since only dominant mutations within OTX2 have been associated with cases of syndromic microphthalmia, retinal dystrophy with or without pituitary dysfunctions, this represents the first report of an OTX2 recessive mutation. Part of the phenotype, including ataxia, myopathy and multiple mitochondrial respiratory chain defects, seemed not related to OTX2 . Further analysis of next generation sequencing (NGS) data revealed additional candidate variants: a homozygous variant in LETM1, and heterozygous rare variants in AFG3L2 and POLG . All three genes encode mitochondrial proteins and the last two are known to be associated with ataxia, a neurological sign present also in the father of the proband. With our study, we aim to encourage the integration of NGS data with a detailed analysis of clinical description and family history in order to unravel composite genotypes sometimes associated with complicated phenotypes.